Diffusion Breast MRI: Current Standard and Emerging Techniques - Mendez, Ashley M.; Fang, Lauren K.; Meriwether, Claire H.; Batasin, Summer J.; Loubrie, Stéphane; Rodríguez-Soto, Ana E.; Rakow-Penner, Rebecca A. (Frontiers in Oncology, 2022)
The role of diffusion weighted imaging (DWI) as a biomarker has been the subject of active investigation in the field of breast radiology. By quantifying the random motion of water within a voxel of tissue, DWI provides indirect metrics that reveal cellularity and architectural features. Studies show that data obtained from DWI may provide information related to the characterization, prognosis, and treatment response of breast cancer. The incorporation of DWI in breast imaging demonstrates its potential to serve as a non-invasive tool to help guide diagnosis and treatment. In this review, current technical literature of diffusion-weighted breast imaging will be discussed, in addition to clinical applications, advanced techniques, and emerging use in the field of radiomics.